Korupsi Dalam Sorotan Hadis Abu Dzar (HR. MUSLIM NO. 1825) dan UU No. 31 Tahun 1999 Tentang Pemberantasan Tindak Pidana Korupsi - Damarudin, Zarqa Haura Bilfaqih; arifin, Tajul (Jurnal Inovasi Global, 2025)
Corruption constitutes a form of abuse of power that causes harm to the state and society. In Islam, trust (amanah) is a fundamental principle of leadership, as emphasized in the hadith of Abu Dzar (HR. Muslim No. 1825), which underscores that leadership is a great trust that can lead to disgrace for those who fail to fulfill it properly. In Indonesia, efforts to eradicate corruption are regulated by Law Number 31 of 1999 on the Eradication of Corruption Crimes, which imposes strict sanctions on perpetrators. This study aims to analyze the relevance of the concept of trust (amanah) as taught in the hadith to Indonesia’s positive law regulations in the context of combating corruption.